Ritual dynamics and religious change in the Roman Empire : proceedings of the eighth Workshop of the International Network Impact of Empire (Heidelberg, July 5-7, 2007) - Hekster, Olivier.; Schmidt-Hofner, Sebastian.; Witschel, Christian. (Impact of Empire, 2009)
This volume presents the proceedings of the eighth workshop of the international network 'Impact of Empire', which concentrates on the history of the Roman Empire and brings together ancient historians, archaeologists, classicists and specialists in Roman law from some thirty European and North American universities. The eighth volume focuses on the impact of the Roman Empire on religious behaviour, with a special focus on the dynamics of ritual. The volume is divided into three sections: ritualising the empire, performing civic community in the empire and performing religion in the empire.